PERCEPTION OF ELECTRIC CAR PRODUCTS ON PURCHASE INTENTION MEDIATED BY TRUST IN JABODETABEK AREA - Aryanto Aryanto; Hery Winoto Tj; Melitina Tecoalu (ID Solutions, 2022)
Cars have become an important mode of transportation for humans, the growth of the automotive industry, especially cars, still sets aside air pollution which is getting higher day by day. The solution to industrial pollution by cars is the emergence of electric car technology. The purpose of this study is to examine consumer perceptions of the interest in buying electric cars which are influenced by trust in Jabodetabek. By using a sample of 100 people who have driven an electric car. The data analysis technique used in this research is inferential statistics as a data analysis tool, namely the PLS (Partial Least Square) approach. The results obtained from this study indicate that consumer perceptions and trust affect the interest in buying electric cars. Consumer perceptions also affect trust and trust mediation variables affect consumer perceptions of purchase intention in electric cars.